Terror landscape threats, challenges & response: South East Asia overview – terrorists systems: methods, capabilities & drivers - El-Muhammady, Ahmad (2022)
The presentation focuses on the terrorism threat landscape in Southeast Asia. Eight key points are highlighted: First, to understand terrorism threats in Southeast Asia, we have to understand the concept of “glorecal”; Second, social and political fragility of Southeast Asia; Third, terrorism and security threats are permanent and evolving variable in the region; Fourth, radicalization and security threats in Southeast Asia, not only religious but also political in nature; Fifth, during COVID-19 pandemic, new form of radicalization emerged to the fore – health-oriented radicalization; Sixth, to what extent the rise of Taliban affects the region?; Seventh, Smart Power approach to fight terrorism; Eighth, we are facing the age of supremacy, not the age of democracy.